Development of a reservoir operation model determining the pre-release strategy for the flood events - Lee, Eunkyung; Yi, Sooyeon; Ji, Jungwon; Hong, Junhwa; Lee, Seonmi; Yoon, Jeongin; Yi, Jaeeung (Journal of Hydroinformatics, 2025)
Floods are among the most prevalent natural disasters, posing significant threats to human activities. Reservoirs can enhance flood control and water conservation by using flood forecast information to prerelease water or adjust storage. However, making timely pre-release decisions that balance reservoir safety and downstream conditions remains challenging. This study aims to develop a reservoir operation model that helps reduce peak releases during the flood season, generate reference tables and graphs for determining target reservoir elevation after pre-release, and propose practical applications for real-time decision-making. We evaluated five flood operation methods (FOMs) using this model and identified FOM V as the most effective. We conducted three case studies on extreme flood events in the Seomjingang reservoir and validated the model using data from the Hapcheon reservoir. The model produces reference graphs and tables to guide operators in determining the target reservoir elevation based on forecasted inflow, updated with each new forecast. The novelty of this study lies in offering a simple, user-friendly tool that enables prompt and reliable reservoir operation during flood events. Our approach supports real-time, proactive reservoir management, reducing downstream flood damage and ensuring sufficient water supply for the dry season.
Keywords: flood control; multipurpose reservoir; pre-release; reservoir operation